Pengembangan Local Intructional Theory Penjumlahan untuk Meningkatkan Kemampuan Numerik Siswa Diskalkulia di Sekolah Dasar - Suci, Dwi Wulan (Jurnal Didaktika Pendidikan Dasar, 2022)
Children who have dyscalculia (difficulty in counting), learning mathematics results are lower than normal children. A learning design is needed that can facilitate their difficulties. This study aims to develop Local Instructional Theory (LIT) with the topic of adding whole numbers. LIT consists of a set of Hypothetical Learning Trajectory (HLT), Learning Implementation Plans (RPP) and Student Worksheets (LKPD). This development uses the Gravemeijer and Cobb model which consists of three stages, namely research preparation, classroom research, and review analysis. Data was collected by means of observation, interviews, document analysis, video documentation and tests and then analyzed qualitatively and quantitatively. The results showed that the LIT product based on Realistic Mathematical Education (RME) for dyscalculia students was in a very valid and practical category with a score of 86.00 and could improve students’ problem solving abilities.